Promoting Interest in Learning Yorùbá Language Using Mobile Game - Oladimeji, Oladosu; Olorunfemi, Temitope; Oladimeji, Olayanju (Journal of Information Technology and Computer Science, 2020)
This paper describes acute areas in which technology plays a role in language and culture revitalization. It was discovered that in order for people to learn a new language, they must express interest in that language. This work presents a new way of arousing the interest of people in learning Yorùbá language through the use of mobile game thereby promoting and revitalizing Yorùbá language and culture. The mobile application was evaluated using questionnaire to selected participants who have the mobile game developed installed on their phones and explored the application, and then rated based on some criteria such as extensibility, ease of use and user interest in learning Yorùbá Language after playing the game. The results showed that 76% of respondents rated the game ease of use as above average, 70% and 90% of the respondents rated the extensibility of the game and interest in learning Yorùbá after playing game above average respectively. This technology-based application will serve as an interesting and fun-filled approach of getting people to express interest in learning native indigenous language individually and as a group.